The Relevance and Challenges of Wasathiyah Islamic Character Education in the Era of Society 5.0 - suharni, Suharni; Iskandi, Iskandi; Noh, Mohd Aderi Cheh (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2025)
This study aims to analyze the strategic relevance of Islamic Wasathiyah (Moderation) Character Education and to identify the substantive challenges of its implementation in confronting information disruption within the Society 5.0 Era. The Society 5.0 concept, which demands a human-centered society, necessitates a strong ethical and moral foundation. This study employs a qualitative methodologi  utilizing a Systematic Literature Review  , collecting and synthesizing data from recent scholarly journals. The findings reveal that the relevance of Wasathiyah is highly functional, where its main pillars act as digital ethical regulators. The principle of Tawazun (balance) ensures that the use of Artificial Intelligence (AI) is directed toward the common good, not dehumanization. Meanwhile, I'tidal (justice) and Tasamuh (tolerance) serve as the foundation for critical literacy and Tabayyun (verification) to counteract extremist narratives and digital disinformation. However, the implementation of Wasathiyah faces dual challenges: 1) Ideological Challenges in the form of narrative competition with extremism in the cyberspace; and 2) Methodological-Technical Challenges caused by the digital competence gap among educators and the digital divide which exacerbates inequality in character education access. The study concludes by emphasizing the urgency of curriculum transformation and enhancing educator competence to ensure Wasathiyah moves beyond a theoretical value to become an effective digital soft skill in guiding the Society 5.0 generation.